IMPACT OF MEDICAL TRAUMA ON PEDIATRIC PATIENTS: A FOCUS ON PAIN AND FEAR MANAGEMENT - Mahmoud, Emad El-Masry (Research Journal of Nursing and Clinical Practice, 2025)
Hospitalization for children disrupts their daily lives and exposes them to a challenging medical environment, leading to anxiety, distress, and potential long-term consequences. This study delves into the impact of pediatric hospitalization on children's well-being, considering their emotional, physical, and developmental aspects. An analysis of the literature reveals that hospitalization can hinder necessary medical procedures in the short term and deter future treatment compliance. Moreover, anxiety-inducing hospital experiences may impede children's growth and emotional development. The study explores how children's reactions to hospitalization are influenced by their age and prior experiences. It is crucial to recognize that hospital rules, routines, and medical interventions can significantly curtail the freedom and independence crucial to a child's development, causing discomfort and unease. This abstract highlight the multifaceted challenges children face during hospitalization, emphasizing the need for tailored support and care to mitigate its adverse effects on their well-being.